Feline Calicivirus Infection with Chronic Stomatitis, Rhinitis and Otitis in a Bengal Cat in Indonesia - Hermawan, Intan Permatasari; Leo, Donna Marie (Faculty of Veterinary Medicine Universitas Brawijaya, 2022)
The purpose of this case study was to describes the infection with feline calicivirus manifested as chronic stomatitis, rhinitis and otitis in a Bengal cat. A cat was presented to the clinic due to inappetence, weakness, and frequent vomiting. It had never been vaccinated, and never been given anthelmintic. It had an open wound on its back, and purulent discharge was appearing in the ear and nose. Using an antigen test kit, Feline Calicivirus was tested positive for infection with Feline calicivirus. Therapies were given to relieve clinical signs however, the patient could not be saved. Prevention of feline calicivirus could be done by vaccination, as well as maintaining cleanliness of housing and equipment.